2023
DOI: 10.1186/s12885-023-11509-7
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 9 (-1237 T/C, -1486 T/C) and the risk of gastric cancer: a meta-analysis of genetic association studies

Yap Zi Qyi,
Htar Htar Aung,
Saint-Nway Aye
et al.

Abstract: Background Gastric cancer has a complex aetiology including genetic factors. Individual case-control studies of toll like receptor (TLR) 9 (-1237 T/C, -1486 T/C) polymorphisms in the gastric cancer risk were available, and they showed variation in the findings. Therefore, we performed a meta-analysis to synthesize the evidence on the association between polymorphisms of TLR 9 (-1237 T/C, -1486 T/C) and the risk of gastric cancer using data from eligible studies. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Evolutionary findings revealed that TLR7 and TLR9 are among the least diverse TLRs genes worldwide, and that mutations affecting these intracellular sensors exert more deleterious effects compared to TLRs expressed on the cell membrane [18]. Several polymorphisms in TLR9 gene, including functional polymorphism -1486 C/T (rs187084), situated in the promoter of the TLR9 gene in 3p21.3 locus, have been associated with cervical and endometrial cancer [19,20], as well as gastric cancer [21,22]. The TLR7 gene polymorphism rs3853839 (C/G), located in the 3 untranslated region (UTR) on X chromosome (Xp22.2), was previously associated with survival in colorectal carcinoma [23].…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary findings revealed that TLR7 and TLR9 are among the least diverse TLRs genes worldwide, and that mutations affecting these intracellular sensors exert more deleterious effects compared to TLRs expressed on the cell membrane [18]. Several polymorphisms in TLR9 gene, including functional polymorphism -1486 C/T (rs187084), situated in the promoter of the TLR9 gene in 3p21.3 locus, have been associated with cervical and endometrial cancer [19,20], as well as gastric cancer [21,22]. The TLR7 gene polymorphism rs3853839 (C/G), located in the 3 untranslated region (UTR) on X chromosome (Xp22.2), was previously associated with survival in colorectal carcinoma [23].…”
Section: Introductionmentioning
confidence: 99%